The evolving role and technique of hip arthroscopy in children and adolescents - Shalin Shah, MS; Tyler Stavinoha, MD; Jeffrey J. Nepple, MD; Allison E. Crepeau, MD; Sasha Carsen, MD, MBA, FRCSC (Elsevier, 2024)
ABSTRACT: Hip Arthroscopy in the pediatric and adolescent hip has evolved from its role as a diagnostic tool to a primary modality of management of variety of hip pathologies in children and adolescents. This article reviews current concepts and advances in hip arthroscopy in this population. We discuss the indications, techniques, outcomes, and complications of hip arthroscopy in children and adolescents. We explore the newer indications of hip arthroscopy in the treatment of SCFE (Slipped Capital Femoral Epiphysis) deformity correction, borderline hip dysplasia, septic arthritis, infantile developmental dysplasia, Perthes disease, and the existing and developing evidence. Finally, we address the challenges and future directions in research, education, and training, unique to the pediatric and adolescent population. Key Concepts: (1) Hip arthroscopy has significant surgical applications in the pediatric and adolescent population, and can be used to help address several intra-articular as well as extra-articular pathologies. (2) The indications and potential for arthroscopic interventions and associated arthroscopic techniques is growing and developing rapidly, along with improving technology, techniques, and training. (3) FAI (Femoro Acetabular Impingement) and labral pathology are the most common indications for surgery in the adolescent, and clinical outcome studies show excellent results. However, nonoperative optimization should be strongly emphasized before surgical consideration. (4) Hip arthroscopy is minimally invasive and relatively low risk, though main risks and complications to be aware of is the potential need for revision or further surgery, transient neuropraxia of the pudendal nerve, surgical site infection, implant/tool-related breakage or failure, failed surgery, and venous thromboembolism. (5) Continued research and innovation in the field of pediatric hip arthroscopy are essential for further improving outcomes and expanding treatment options for young patients with hip disorders, and more pediatric-specific clinical research is needed.